Analisis Kemampuan Penalaran Matematis Siswa Materi Balok dan Kubus melalui Pembelajaran Model Think Pair Share Berbantuan Problem Card - Chusna, Cahya Amalia (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research is motivated by the importance and still not optimal mathematical reasoning ability (KPM). This research aims to test the mathematical reasoning abilities of class VI students on blocks and cubes using the Think Pair Share model of learning with the help of problem cards, achieving learning mastery and describing the mathematical reasoning abilities of class VI students on blocks and cubes using the Think Pair Share model of learning with the help of Problem Cards. The method used is a mixed methods concurrent triangulation design. Data collection techniques use observation, tests and interviews. The population is class VI students at MI Khozinatul Ulum Blora with a sample of class VIA students as the research class. The research subjects were two students each with high group reasoning ability (KPA), medium group reasoning ability (KPS), and low group reasoning ability (KPK). The results of the research show that learning using the Think Pair Share model assisted by problem cards achieves learning completeness. KPA students master all KPM indicators, KPS students master three KPM indicators and KPK students lack mastery of all KPM indicators.